Transpharyngeal Exposure of GnRH Neurons - Stephanie Constantin; Allan Herbison (Bio-Protocol, 2014)
The neurons secreting gonadotropin-releasing hormone (GnRH) control fertility in all mammalian species. However, investigations of this neuronal population are difficult as the cell bodies of the approximately 800 GnRH neurons are scattered through the basal forebrain ranging from the olfactory bulbs through to the base of the hypothalamus. While acute brain slice preparations enable the electrophysiological characteristics of these cells to be determined in vitro, their topography has made investigations in vivo extremely difficult. We detail here a surgical approach that allows GnRH neurons at the base of the hypothalamus to be assessed in vivo in the anesthetized mouse (Figure 1). This procedure enables electrical recordings to be made from neurons located on the ventral surface of the mouse brain (Constantin et al., 2013).